Shameful Victory : The Los Angeles Dodgers, the Red Scare, and the Hidden History of Chavez Ravine - Laslett, John H. M. (Book collections on Project MUSE., 2015)
"The book offers a history of Chavez Ravine with special attention to the period after World War II to the early 1960s, studying Los Angeles and its political structure, the contractions in policies around public housing, the impact on Mexican Americans, and the building of Dodger Stadium and the arrival of the team to Chavez Ravine"--Provided by publisher